First record of Blankaartia sinnamaryi (Floch & Fauran, 1956) (Trombidiformes: Trombiculidae) parasitizing the striped owl in Northeastern Brazil - Bassini-Silva,Ricardo (2021)
Abstract The chigger species Blankaartia sinnamaryi (Floch & Fauran) has been collected mainly from birds with a few records from reptiles and mammals. In Brazil, this species has been found on birds in the Minas Gerais and Rio de Janeiro states. Here, we report the first record of B. sinnamaryi parasitizing the striped owl, Pseudoscops clamator (Vieillot), in the Paraíba state, Brazil (northeastern region).